Application of Date Palm Surface Fiber as an Efficient Biosorbent for Wastewater Treatment. Issue 1 (7th December 2022) - Al Arni, Saleh; Elwaheidi, Mahmoud; Converti, Attilio; Benaissa, Mhamed; Salih, Alsamani A. M.; Ghareba, Saad; Abbas, Nadir
Abstract: The significance of using date palm surface fiber as a biosorbent to remove pollutants from wastewater is evaluated. This material, which has advantages over other natural adsorbing materials, for being inexpensive, renewable, eco‐friendly, and available in large scale worldwide, has been widely used for the removal of several types of pollutants such as acid and basic dyes, heavy metals, pesticides, oils, and organic compounds. In addition to its use as an effective biosorbent to remove pollutants from wastewater, date palm surface fiber exhibits wide future perspectives in several other applications. Abstract : Date palm surface fiber is inexpensive, renewable, eco‐friendly, and available in large scale worldwide. Its potential use as biosorbent material for wastewater treatment is overviewed and discussed. Surface fiber is widely used for removal of several types of pollutants from water such as acid and basic dyes, pesticides, oils, and organic compounds, and has a high adsorption capacity of heavy metals.